Susu Steril Kurma Minuman Sehat untuk Masa Pandemi Covid-19: Studi Takhrij dan Syarah Hadis Pendekatan Bidang Kesehatan - Fuziawatie, Asti Sovie (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the hadith syarah related to sterile date milk as a healthy drink during the Covid-19 pandemic. This study uses a qualitative approach that emphasizes literature study through the takhrij and syarah hadith methods with contemporary analysis. The results of this study found that the quality status of the hadith about dates is considered valid according to the takhrij hadith. Meanwhile, the hadith syarah shows that dates are known to be processed ingredients for health drinks, including sterile date milk which is useful for increasing immunity during the Covid-19 pandemic. The conclusion of this study is that the hadith about dates can be referred to as an Islamic practice because it has a valid status and dates can be used as sterile date milk products to increase immunity during the Covid-19 pandemic according to health sector instructions. This study recommends the collaboration of hadith experts and health experts in experimental processing of sterile dates milk for health during the Covid-19 period.